A systematic review and meta-analysis of the effects of green tea extracts and polyphenols in female hormone-dependent cancers for benefit-risk evaluation - He, Jin-jing; Zhang, Yan-fang; He, Ze-huang; Zheng, Lei (Frontiers in Oncology, 2025)
Female hormone-dependent cancers rely on estrogen for growth and include breast, uterine and ovarian cancers. Although preclinical studies indicate that green tea extracts and polyphenols derived from green tea exhibit anti-tumor effects without mimicking estrogen like phytoestrogens, clinical evidence remains scarce. To explore the potential of green tea products in inhibiting these cancers, we conducted a meta-analysis of preclinical data. We evaluated the effects of green tea extract (GTE), green tea polyphenol-enriched product (GTP), and epigallocatechin gallate (EGCG) on tumor growth indices in mouse and rat models of breast, ovarian, and uterine cancers. A comprehensive search of PubMed, Web of Science, and Google Scholar (1998–2024) identified 20 studies for inclusion. Pooled analysis showed significant reductions in tumor volume (Hedge’s g = -2.332, 95% CI = -3.067 to -1.596, p = 0.000) and tumor weight (Hedge’s g = -2.105, 95% CI = -2.746 to -1.463, p = 0.000). Subgroup analysis revealed that GTE and EGCG reduced breast and ovarian tumors, while EGCG had no significant impact on uterine cancer. Significant heterogeneity was observed across studies. No consistent adverse effects were reported in the included studies, though liver function parameters were not assessed. These findings highlight the necessity for targeted clinical trials to assess the distinct benefits of each tea-based product for various cancer types.